Arthritis in leprosy without specific skin lesion - Dewi, Sumartini; Setiyohadi, Bambang (Indonesian Journal of Rheumatology, 2010)
Leprosy patients could display a great variability of signs and symptoms. An overabundance of rheumatic manifestations, occuring alone or in varying combinations, are associated with leprosy, particularly with lepra reactions A study involving seventy cases of leprosy found that rheumatic manifestations were seen in 61.42% of cases: arthritis in 54.28% and soft tissue rheumatism in 17.14%. Enthesitis was seen in 2.84% of cases. Rheumatic manifestations may be the primary complaint, thus delaying accurate diagnosis. Musculoskeletal involvement in leprosy is the third most frequent manifestation after dermatological and neurological involvements. It can occur at anytime during the infection. Articular inflammation in leprosy, which closely mimics other rheumatic disorders, usually occurs in reactive states, particularly erythema nodosum leprosum (ENL).1 About 1â5% of leprosy patients are reported of developing arthritis (synovial inflammation) at some stage of the disease but this rate increases to over 50% during lepra reactions.2 Here we report a case of arthritis in leprosywithout any typical skin lesion thus causing a delay in diagnosis.